Novel yellowish-green light-emitting Ca10(PO4)6O:Ce3+ phosphor: structural refinement, preferential site occupancy and color tuning. Issue 16 (1st February 2016) - Li, Guogang; Zhao, Yun; Wei, Yi; Tian, Ying; Quan, Zewei; Lin, Jun
Abstract : Novel yellowish-green emitting Ca10 (PO4 )6 O:Ce 3+ phosphor are obtained through controlling the preferential site occupancy of Ce 3+ ions. Abstract : Here we report a novel Ca10 (PO4 )6 O:Ce 3+ phosphate phosphor, consisting of an apatite structure, whose emission peaks under excitation with near-ultra violet light were found to shift from 410 nm (blue light) to 510 nm (yellowish-green light) with an increasing Ce 3+ doping level due to the Ce 3+ at the different concentrations preferentially occupying different crystallographic sites.